API Compatibility Issue Detection, Testing and Analysis for Android Apps - Mahmud, Tarek (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2021)
Android apps are developed using a Software Development Kit (SDK), where the Android application programming interface (API) enables app developers to harness the functionalities of Android devices by interacting with services and hardware. However, API frequently evolves together with its associated SDK. The mismatch between the API level supported by the device where apps are installed and the API level targeted by app developers can induce compatibility issues. These issues can manifest themselves as unexpected behaviors, including runtime crashes, creating a poor user experience. Recent studies investigated API evolution to ensure the reliability of the Android apps, however, they require improvements. This work aims to establish novel methodologies that will improve the state-of-the-art compatibility issue detection and testing approaches.